STANDAR PELAYANAN MINIMAL WAKTU TUNGGU DI PENDAFTARAN PASIEN RAWAT JALAN DI RSUD PETALA BUMI PROVINSI RIAU - Henny Maria Ulfa (LPPM Universitas Muhammadiyah Riau, 2017)
The waiting time is the time it takes from the patient to register until the medical record file is sent to the polyclinic. RSUD Petala Bumi Provinsi Riau for service still not good because it still uses manual system. Minimum standards of service time wait patients in outpatient registrationin RSUD PetalaBumiProvinsi Riau.Research methodology used in this research is descriptive approach with a combination of quantitative and qualitative, samples to this research a total of 97 patients. Produce research waiting time in registration outpatients included in a category slow(≥ 10 minute) as much as 66 patients (68,0 %)While in the category of fast(≤ 10 minute) 31 patients (31,9 %). From 97 outpatients at the hospital Petala Bumi,riau.Seen from workload by officers additional resources is needed, especifically at distribution so that the medical officerno longer working concurrently again, education and training record medical officer has already been done, SPO in TPPRJ already exists but not run optimally, and facilities in unit medical record hospital in Petala Bumi Riau has been sufficient. Advice on this research is should be increased again the quality and quantity of the of officer so that patient do not wait longer in registration of outpatient. For medical officers are expected to perform their duties in accordance with SOPs that have been established so as to increase the value of productivity so that patient services faster and can improve the quality of service in TPPRJ.